Analisa Kecepatan Transfer Data Pada Perancangan Hotspot Sederhana Dengan System Single Sign On Di Perkantoran - Bela Neziah Arum Pangesti (Universitas Darussalam Gontor, 2017)
The problems office in the utilization of wireless technology has widely used but sometimes without take into the number of users, so it is not mangkus. The networking system for small office can be use wireless simple system. Most of the office has applied hotspot but that is old system, one account for all people using internet access. Single sign-on is a system services of hotspot, this system verifying an account for each user so people have different and username dan a password. The methodology used is literature review, analysis, design, implementation, testing and analysis of the data transfer rate. The hotspot with a single sign-on system using mikrotik, and access point, the connected with networking devices in the office. Winbox tools is used to configuration. Testing with the user had been connected to the hotspot system single sign on. Methods of test to user login on the system single sign-on is the black box texting. Testing the speed of data transfer is used staff user and guest user who uploaded three types of files to the drive with diffrent bandwidth. Then the network sniffing is used tools wireshark. The results from this study is simple hotspot service with single sign-on system for office and from the analysis of the data transfer rate was known the data transfer rate on the staff user and guest user to the three types of file is a type of word files greater than PDF and PPT.